Primary or secondary? Regionalism's multiple roles in Brazil's international emergence - Clarkson, Stephen (2016)
Abstract: Of all the countries identified as rising powers on the world stage, Brazil appears to have drawn considerable economic and political strength from its engagement with various forms of regionalism during the expansionist years when Lula was president. Whether by helping create a local, intra-regional entity (Mercosul) or, later, proposing a continental one (UNASUL), Brasilia appeared to have the capacity to further its own economic and political interests by generating cooperative interactions with its smaller neighbors. Subsequently it took a leading role in inter-regional negotiations between Mercosul and the European Union in the global North and between Mercosul and ASEAN in the global South. More recently still, it spread its wings by associating trans-regionally with powers that are similarly dominant within their own regions – IBSA (India, Brazil, and South Africa) and BRICS (Russia, India, China, and South Africa) which shared with it a desire to play greater roles in the m